PERAN EVALUASI DALAM MENINGKATKAN KUALITAS PENDIDIKAN AGAMA ISLAM DI ERA DIGITAL - Agustina, Intan Pramudya; Yuana, Ochi Aprila (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
Evaluation is an essential component of the learning process, functioning to assess both students’ achievement and the effectiveness of instruction. Its purpose extends beyond academic measurement to encompass student development in cognitive, affective, and psychomotor domains. Within the framework of Islamic Religious Education (PAI), evaluation is particularly vital for nurturing Islamic values and fostering students' character holistically—intellectually, emotionally, and spiritually. The objective of this research is to analyze the role of evaluation in improving the quality of Islamic Religious Education, particularly in the digital era. It seeks to investigate how educators incorporate technology into their evaluation practices and the extent to which these practices align with educational standards and values of Islam. This study employs a qualitative library research method, supported by content analysis of scholarly literature and previous empirical studies. The data were collected from books, journal articles, and educational policy documents relevant to digital learning evaluation and Islamic pedagogy. The findings reveal that while the integration of technology—such as Learning Management Systems (LMS), online quizzes, and real-time assessments—offers efficiency and accessibility, many educators still rely heavily on traditional evaluation methods that focus primarily on the cognitive domain. This results in a disconnect between the intended educational outcomes and actual practices. Furthermore, the lack of digital literacy and spiritual integration in evaluation tools poses a significant challenge in achieving meaningful educational impact. As a conclusion, the study underscores the need for comprehensive evaluation strategies that are not only technologically adaptive but also spiritually grounded. A well-designed evaluation system in PAI should serve as both a diagnostic tool and a transformative instrument—empowering teachers to guide students in achieving excellence in both academic competence and Islamic character. Enhancing educators’ capacity in digital assessment is essential to cultivating a generation that is morally upright and resilient in the face of global and technological change.